Effect of Collaborative Learning Strategies on Student Achievement in Various Engineering Courses - Geraldine Gonzaga Nerona (International Journal of Engineering Education, 2019)
This study focused on determining the effectiveness of collaborative learning strategies in improving students' performance in three general engineering courses. The pretest-posttest control group experimental design was used in the study. From the results of the Z-test, there were no significant differences in the pretest scores of the experimental and control groups. However there were significant differences in the posttest scores of the respondents, with the experimental groups engagedin collaborative learning obtaining significantly higher achievement scores than their control group counterparts,who were exposed to the traditional lecture-discussion and individual learning methods. Effect sizes were also positive for the experimental groups, meaning, they were able to perform better in class compared to their control group counterparts.